Percutaneous Insertion of Peritoneal Ports. Issue 2 (1st February 2012) - Greben, Craig R.; Goldstein, Greg E.; Lovecchio, John; John, Veena; Putterman, Daniel; Caplin, Drew; Gandras, Eric J.
Abstract : Objective: To describe a technique for image-guided percutaneous insertion of peritoneal ports in patients without ascites who have undergone surgical debulking for stage III ovarian cancer. Materials and Methods: Between 2006 and 2010, 29 intraperitoneal ports were placed percutaneously in 29 patients who presented after debulking surgery for stage III ovarian cancer. Ultrasound and fluoroscopy guidance were used to assist in the port placement. Results: We demonstrated a technical success rate of 100% in 29 patients. The ports remained in place for an average of 186 days; and during that time, only 2 complications (6.9%) arose. One patient presented with kinking and looping of the catheter/port reservoir connection, and the redundant loop was removed. The other patient presented with a suspected wound infection over the port pocket, and the port was removed. Conclusions: Placement of percutaneous intraperitoneal ports is feasible with an acceptably low complication rate of 6.9% in patients without abdominal ascites.